Interactive Methods for Developing Problem-Solving Skills in Visual Arts Education - Gadoyev Ibrohim Niyozovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the use of interactive teaching methods to develop problem-solving skills in visual arts education. It examines how collaborative activities, project-based learning, and digital tools can foster students’ creativity, critical thinking, and artistic competencies. The study highlights pedagogical strategies that enhance student engagement, independent thinking, and the ability to generate innovative artistic solutions.